Life Skills Education as a Strategy for Women’s Empowerment: A Case Study of Anggrek Bulan Community Learning Center - Wiwin Yulianingsih Wiwin Yulianingsih; Sjafiatul Mardliyah; Ali Yusuf; Shobri Firman Susanto; Ganes Gunansyah; Mustakim; Mita Lutviatiani; Ikhwan Fadlu Fantazilu (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2026)
Abstract: Women's empowerment is a crucial issue in achieving gender equality as outlined in the 2030 Sustainable Development Goals (SDGs). One relevant strategy is life skills based non-formal education, which provides opportunities for women to improve their skills, independence, and self-confidence. This study aims to describe the implementation of the life skills program, analyze its impact, and identify supporting and inhibiting factors at the Anggrek Bulan Community Learning Center in Banyuwangi. The study employed a case study approach with participatory observation, in-depth interviews, and documentation techniques. Data analysis applied the Miles and Huberman model. The results show that the life skills program was designed in a participatory manner according to the needs of the learners, involving women from planning to evaluation. The impacts include improved technical skills (sewing, batik, digital marketing) and soft skills (public speaking, leadership), enabling women to become more independent and able to develop businesses. In conclusion, life skills education at the Anggrek Bulan Community Learning Center effectively strengthens women's capacity and role, while also serving as a model for contextual and sustainable empowerment. Keywords: Gender Equality, Life Skills Program, Nonformal Education, Women’s Empowerment